2003
DOI: 10.1086/376982
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and Physical Properties of a Post–Coronal Mass Ejection Current Sheet

Abstract: In the eruptive process of the Kopp-Pneuman type, the closed magnetic field is stretched by the eruption so much that it is usually believed to be '' open '' to infinity. Formation of the current sheet in such a configuration makes it possible for the energy in the coronal magnetic field to quickly convert into thermal and kinetic energies and cause significant observational consequences, such as growing postflare/CME loop system in the corona, separating bright flare ribbons in the chromosphere, and fast ejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
279
3
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(323 citation statements)
references
References 80 publications
39
279
3
2
Order By: Relevance
“…Different mechanisms could give rise to the same output. For example, Sweet-Parker CS with anomalous resistivity Biskamp 2000;Priest and Forbes 2000), Petschek-type reconnection (Petschek 1964;Biskamp 1986;Forbes and Priest 1987;Yokoyama and Shibata 1994;Kulsrud 2001;Drake et al 2006;Baty et al 2009;Vršnak et al 2009;Zweibel and Yamada 2009;Ko et al 2010;Liu et al 2012), and turbulent reconnection (Strauss 1988;Bhattacharjee and Yuan 1995;Lazarian and Vishniac 1999;Lin et al 2007Lin et al , 2009Lazarian et al , 2014. These different dissipation styles may even work together to yield a much more complex pattern and more efficient diffusion than that dominated only by a single mechanism (e.g., see also Mei et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different mechanisms could give rise to the same output. For example, Sweet-Parker CS with anomalous resistivity Biskamp 2000;Priest and Forbes 2000), Petschek-type reconnection (Petschek 1964;Biskamp 1986;Forbes and Priest 1987;Yokoyama and Shibata 1994;Kulsrud 2001;Drake et al 2006;Baty et al 2009;Vršnak et al 2009;Zweibel and Yamada 2009;Ko et al 2010;Liu et al 2012), and turbulent reconnection (Strauss 1988;Bhattacharjee and Yuan 1995;Lazarian and Vishniac 1999;Lin et al 2007Lin et al , 2009Lazarian et al , 2014. These different dissipation styles may even work together to yield a much more complex pattern and more efficient diffusion than that dominated only by a single mechanism (e.g., see also Mei et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several early versions of the two-ribbon flare configuration could be found in the work of Švestka and Cliver (1992). It is now known that the motions of the flare ribbons and loops are not due to mass motions of the plasma but rather due to the upward propagation of the energy source onto new magnetic field lines at higher altitudes (Schmieder et al 1987); the hot X-ray loops are the newly reconnected closed loops, located at the outermost edge of the loop system, mapping to the outer edge of the flare ribbons; while the cool Hα loops are formed from the hot ones by conductive and radiative cooling (see Ko et al 2003 and references therein for a brief review on this issue). (Note: The term "altitude" used in this paper means the distance measured from the surface of the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…Following Ciaravella et al (2002), Ko et al (2003) and Webb et al (2003), the current sheet developing in the wake of a CME is investigated once again. The event discussed here occurred on the east limb of the Sun on November 18, 2003.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Utilizing the ultraviolet spectroscopic observations from the Ultraviolet Coronagraphic Spectrometer (UVCS) on board the Solar and Heliospheric Observatory (SOHO), together with other remote-sensing data, Ciaravella et al (2002) and Ko et al (2003) conducted comprehensive analyses from various aspects on several eruptive processes that clearly manifested both coronal mass ejections (CMEs) and solar flares, and confirmed the existence and development of the long current sheet in the events as predicted by Lin & Forbes (2000). Webb et al (2003) surveyed 59 CMEs observed by the Solar Maximum Mission from 1984 to 1989, and found that about half were followed by co-axial, bright rays suggestive of newly formed current sheets.…”
Section: Lin Et Almentioning
confidence: 99%
See 1 more Smart Citation